A Metal‐Bridged Tricyclic Aromatic System: Synthesis of Osmium Polycyclic Aromatic Complexes1. Issue 24 (29th April 2014) - Zhu, Congqing; Zhu, Qin; Fan, Jinglan; Zhu, Jun; He, Xumin; Cao, Xiao‐Yu; Xia, Haiping
Abstract Aromaticity is one of the most important concepts in organic chemistry. A variety of metalla‐aromatic compounds have been recently prepared and in most of those examples, the metal participates only in a monocyclic ring. In contrast, metal‐bridged bicyclic aromatic molecules, in which a metal is shared between two aromatic rings, have been less developed. Herein, we report the first metal‐bridged tricyclic aromatic system, in which the metal center is shared by three aromatic five‐membered rings. These metalla‐aromatics are formed by reaction between osmapentalyne and arene nucleophiles. Experimental results and theoretical calculations reveal that the three five‐membered rings around the osmium center are aromatic. In addition, the broad absorption bands in the UV/Vis absorption spectra of these novel aromatic systems cover almost the entire visible region. This straightforward synthetic strategy may be extended to the synthesis of other metal‐bridged polycyclic aromatics.